2000
DOI: 10.1002/1096-9861(20001211)428:2<191::aid-cne1>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of mRNAs encoding CRF receptors in brain and pituitary of rat and mouse

Abstract: Two G protein-coupled receptors have been identified that bind corticotropin-releasing factor (CRF) and urocortin (UCN) with high affinity. Hybridization histochemical methods were used to shed light on controversies concerning their localization in rat brain, and to provide normative distributional data in mouse, the standard model for genetic manipulation in mammals. The distribution of CRF-R1 mRNA in mouse was found to be fundamentally similar to that in rat, with expression predominating in the cerebral co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

68
823
8
11

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 963 publications
(915 citation statements)
references
References 83 publications
68
823
8
11
Order By: Relevance
“…The observed hypothalamic site of anorectic action for Ucn 3 is supported by neuroanatomical studies, which have observed high levels of CRF 2 receptor synthesis and binding in the rat hypothalamus (Van Pett et al, 2000;Heinrichs et al, 2001). The dorsomedial VMN is rich with CRF 2 receptors (Van Pett et al, 2000) and Ucn 3 terminals (Li et al, 2003), and medial parvocellular (Chalmers et al, 1995) or magnocellular PVN neurons (Van Pett et al, 2000) also reportedly express moderate CRF 2 mRNA levels.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The observed hypothalamic site of anorectic action for Ucn 3 is supported by neuroanatomical studies, which have observed high levels of CRF 2 receptor synthesis and binding in the rat hypothalamus (Van Pett et al, 2000;Heinrichs et al, 2001). The dorsomedial VMN is rich with CRF 2 receptors (Van Pett et al, 2000) and Ucn 3 terminals (Li et al, 2003), and medial parvocellular (Chalmers et al, 1995) or magnocellular PVN neurons (Van Pett et al, 2000) also reportedly express moderate CRF 2 mRNA levels.…”
Section: Discussionmentioning
confidence: 75%
“…The dorsomedial VMN is rich with CRF 2 receptors (Van Pett et al, 2000) and Ucn 3 terminals (Li et al, 2003), and medial parvocellular (Chalmers et al, 1995) or magnocellular PVN neurons (Van Pett et al, 2000) also reportedly express moderate CRF 2 mRNA levels. Single-unit recording studies of hypothalamic slices found that stresscopin-related peptide, structurally related to Ucn 2, alters firing rates of neurons in the VMN and PVN, supporting their functional sensitivity to CRF 2 stimulation (Davidowa and Plagemann, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both CRH and CRH-related neuropeptides exert their influence on CRH 1 and CRH 2 (Lovenberg et al, 1995;Van Pett et al, 2000;Dautzenberg and Hauger, 2002). CRH is relatively selective for the CRH 1 receptor with moderate affinity to the CRH 2 receptor (Timpl et al, 1998) whereas Ucn1 has high affinity to both CRH 1 and CRH 2 receptors (Timpl et al, 1998), but relatively greater affinity for CRH 2 receptors Reyes et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…central amygdala) and brain stem, inter-connected by CRF-stained fibres in medial forebrain bundle; and scattered CRF-stained cells throughout most areas of the cerebral cortex. An extensive in situ hybridization mapping study of mRNAs for CRF receptor type 1 (CRF-R1) and type 2 (CRF-R2) has been conducted in rat and mouse brains and pituitary glands (Van Pett et al, 2000): in both species, CRF-R1 exhibits high expression in the pituitary and a wide distribution throughout the CNS with regions of high expression including prefrontal cortex, amygdala, bed nucleus of stria terminalis (BNST), septum, basal ganglia, brain stem (e.g. periaqueductal gray, pre-and post-cerebellar regions) and cerebellum.…”
mentioning
confidence: 99%